Research areas for housing consumer behavior: from housing mobility to post-ocuppancy evaluation - Freitas, Ana Augusta Ferreira de (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper aims at expanding the theoretical background on marketing research in construction. Literature review shows that national efforts are focused just on market research and post-occupancy evaluation, while international literature provides a wide range of examples on residential mobility, housing search, housing tenure, housing preferences, housing choice models and housing satisfaction. A diagram is proposed depicting how potential clients took decisions about their housing careers, starting with mobility triggers and ending with post-occupancy satisfaction. Drawing a parallel review on international and national literature on the issue will help to redirect and foster research on housing by the Brazilian academic community, increasing the range of methodologies that might be used, deepening statistical resources and understanding behavioral attitudes of potential clients in relation to their present and desired dwelling.